Soil Native C/N Ratio Affects Diazotrophic Bacterial Composition and N Fixation by Regulating SOC Distribution in Soil Particles After Residue Incorporation - Pengfei Duan; Di Zhao; Shuqiong Yang; Jibao Chen; Zhaojin Chen; Lingling Cao (Microorganisms)
Residue incorporation is a universally accepted agronomic practice around the world. However, the relationship between C and N turnover in soil is still not fully understood. We performed a soil microcosm incubation experiment to study the effects of residue incorporation with different C-to-N ratios (C/N) (low, 31.8; high, 84.5) on the SOC distribution, diazotrophic bacterial composition, and N accumulation in different particle size fractions (PSFs) of three types of soil parent material with different native C/N ratios. Our results demonstrate that SOC is 1.34 to 2.50 times more easily retained and accumulated in clay compared to baseline levels at the early stage of soil development. The native C/N ratio markedly affects the microbial metabolic characteristics and the SOC accumulation processes. Specifically, low C/N residue enhanced SOC accumulation in high-native-C/N soil, while the high-C/N residue maximized SOC in low-native-C/N soil. These shifts regulated the composition of the diazotrophic bacterial community, increasing the nitrogenase coding gene (nifH) abundance 5.57- and 8.1-fold in low-C/N residue treatments and 6.6-fold in the high-C/N residue treatment, thereby promoting soil N accumulation. Moreover, we highlight the potential role of Bradyrhizobiaceae, Rhodospirillaceae, Micrococcaceae, Rhizobiaceae, Comamonadaceae, Nitrospiraceae, and Burkholderiaceae in biological N fixation during pedogenesis. This study explored the coupling relationship between soil native and residue C/N and soil biological N fixation at the soil particle level, and the results suggest that residue incorporation to improve soil fertility needs to be further explored according to soil native C/N.